Characterization and utilization of water treatment sludge for coagulation of raw water - Kabelo Lebogang; Freeman Ntuli; Tumeletso Lekgoba; Vepika Kandjou; Mpho Tsie (Water Science and Technology, 2023)
One of the critical steps in the treatment of raw water for human consumption is clarification. It encompasses coagulation and flocculation to reduce the concentration of suspended solids in turn producing a semi-solid slurry called water treatment sludge (WTS). It is necessary to characterize and find economic and sustainable ways to utilize the WTS. The WTS used in this work was characterized and contained aluminum (Al) (20.3% Al2O3) and iron (Fe) (5.28% Fe2O3) making it suitable for the development of a coagulant. A less energy-intensive way, through atmospheric acid leaching of WTS, was developed to extract Al and Fe for use as a coagulant. The sulphuric acid concentration and solid loading that gave the highest Al concentration were determined to be 3N and 5 g/100 mL, respectively. Turbidity reduction achieved with the developed coagulant ranged from 91 to 99% and was higher than that obtained in related studies due to the higher concentrations of Al and Fe in the WTS used in this study. Since the coagulant was very acidic, it was co-dosed with calcium oxide at 10 g/L of water to adjust the pH of the final water to allowable pH values for potable water (6.5–9.5). HIGHLIGHTS Water-treated sludge (WTS) can be leached to produce a coagulant.; WTS is rich in aluminum which is essential for coagulation.; Acid leaching effectively extracted 35.7 mg/g Al and 4.5 mg/g Fe from WTS.; > 90% turbidity reduction was achieved for low, medium and high turbid water.; WTS can be used in other applications based on its Al, Fe and Si content.;